Analisis Pengaruh Penggunaan Cooler Peltier Terhadap Performa Ponsel saat Menjalankan Game Mobile Legends : Bang Bang dengan Variasi Resolusi Grafik - I Made Yudi Dharmawan; Made Sutha Yadnya; Djul Fikry Budiman (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2026)
This research covers the measurement and analysis of the effect of peltier coolers on mobile phone performance while playing Mobile Legends: Bang Bang. System stability control conditions can lower the Frames per Second (FPS) in the image display (lag). Direct data collection is in the form of quantitative experimental. The use of two mid-range phones was tested with a variety of graphics resolutions (Standard and HD), durations of 10, 15 and 20 minutes, as well as conditions with and without coolers. Each combination of treatments was repeated 30 times. The data was analyzed by comparing the average temperature drop and the FPS increase, so that a deep correlation value (R²) was obtained, a term used to measure the correlation between temperature and FPS. The results showed that peltier coolers were effective in lowering the temperature significantly. On Xiaomi, the average temperature drop is 9,24°C (Standard) and 12,02°C (HD), with an increase in FPS of 0,23 and 14,08. On Infinix, the temperature drop is 9.19°C (Standard) and 10.92°C (HD), with an increase in FPS of 0.011 and 1.023. An R² value close to +1 indicates a strong correlation between a decrease in temperature and an increase in FPS.